PENGARUH BRAND IMAGE, AWARENESS DAN TRUST TERHADAP KEPUTUSAN PEMBELIAN MELALUI DIGITAL MARKETING PADA PRODUK DUPA HARUM GROSIR - Ni Luh Indiani; Ni Wayan Ari Sudiartini; Ni Komang Ayu Tri Utami (LP2M Universitas Bina Bangsa, 2022)
The increasing competition in marketing for product and service categories, there is also competition in terms of brands. A brand must be able to build a sense of trust (brand trust) for its consumers. The way the company is to maintain the products and services it produces is to create a brand image. A good brand image will increase consumer confidence in a product or service, giving rise to the desire to better know and remember a particular product or service. The purpose of this study is to find out the influence of brand image, awareness and trust on the purchasing decisions of Wholesale IncenseProducts. The research method in this research is a quantitative approach. Data collection methods use literature studies, field studies and questionnaires. The population uses consumers of Wholesale Fragrant Incense Products, a sample used by as many as 60 respondents. The data analysis techniques used are Validity Test, Rehabilitation, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, Test t and Test F. The results of this research brand image, awareness and trust have a positive and simultaneous significance on purchasing decisions through Digital Marketing on Incense Products. By having Brand Image, Awareness and Trust can increase purchase decisions in buying on Incense Fragrant Wholesale products